Mnemonic ecologies : memory and nature conservation along the former Iron Curtain - Pieck, Sonja K. (The MIT Press, 2023)
The first book-length scholarly treatment of Germany's largest conservation project, the Green Belt, the volume by Sonja Pieck presents a new interdisciplinary approach: that effective restoration and conservation of wounded land must merge ecology with memory. Since the Cold War's end in 1989, German conservationists have transformed the once-militarized border between East and West Germany into an extensive protected area. Yet as forests, meadows, and wetlands replace fences, minefields, and guard towers, ecological recovery must reckon with the pain of the borderlands' brutal past. The lessons gained by conservationists here, Pieck argues, have profound practical and ethical implications far beyond Germany.